2014
DOI: 10.1007/s10815-014-0397-7
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum thyroid-stimulating hormone is associated with decreased anti-Müllerian hormone in infertile women of reproductive age

Abstract: Purpose Thyroid dysfunction and autoimmune thyroiditis are associated with fertility in women of reproductive age. AntiMüllerian hormone (AMH), a known biomarker of ovarian function, may be affected by impaired thyroid function; however, the relationship between AMH and thyroid hormone has not been elucidated. Methods In this case-control study, to identify the impact of thyroid hormone on ovarian reserve, we recruited 67 consecutive Japanese infertile patients and 27 normal fertile women aged 30-39 years with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 25 publications
3
40
3
1
Order By: Relevance
“…We enrolled 174 infertile patients with high TSH levels, excluding women with factors impacting thyroid and ovarian function. According to previous reports, an increased serum TSH level is associated with diminished ovarian reserve in infertile women . We speculated that LT4 replacement adequately suppresses excess TSH secretion, leading to an improvement in impaired ovarian function and AMH level in patients with subclinical hypothyroidism.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…We enrolled 174 infertile patients with high TSH levels, excluding women with factors impacting thyroid and ovarian function. According to previous reports, an increased serum TSH level is associated with diminished ovarian reserve in infertile women . We speculated that LT4 replacement adequately suppresses excess TSH secretion, leading to an improvement in impaired ovarian function and AMH level in patients with subclinical hypothyroidism.…”
Section: Resultsmentioning
confidence: 89%
“…In particular, an aberrant increased serum TSH level is associated with a high prevalence of diminished ovarian reserve in infertile women . In infertile women, the TSH level is inversely correlated with anti‐Müllerian hormone (AMH), which is produced by granulosa cells of primary developing follicles and is a known biomarker of ovarian function, excluding those with factors impacting on thyroid and ovarian function . In in vivo research, hypothyroidism has an adverse effect on folliculogenesis, granulosa cell differentiation and steroidogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…This study findings are well in line with the previous studies on relation between AMH and primordial follicle count. 6,9 These studies revealed an inverse correlation between TSH and AMH levels in infertile women with decreased ovarian function without other factors affecting thyroid and ovarian function. 6,9 Cramer et al showed that TSH acts as predictor of fertilization failure in women undergoing IVF.…”
Section: Discussionmentioning
confidence: 94%
“…Cases were chosen from patients who visited the fertility outpatient clinic at the department of Obstetrics and Gynaecology of S.V.S Medical and Hospital and were diagnosed as infertile according to the previously established criteria were recruited into this study. 6 We also consecutively recruited 30 age matched normal fertile women aged 21 -35 years. They had no history of treatment for infertility or thyroid disorders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation